State of the world's forests, 2011
Summary: "The ninth biennial issue of State of the World's Forests, published at the outset of 2011, the International Year of Forests, considers the theme 'Changing pathways, changing lives: forests as multiple pathways to sustainable development'. It takes a holistic view of the multiple ways in which forests support livelihoods. The chapters assembled for this year's State of the World's Forests highlight four key areas that warrant greater attention: regional trends on forest resources; the development of sustainable forest industries; climate change mitigation and adaptation; and the local value of forests. Considered together, these themes provide insights on the true contribution of forests to the creation of sustainable livelihoods and alleviation of poverty"--Publisher website